Letramento na escola indígena Kaiapó - Silva, Maria Lucia Gomes da (2022)
The work analyze how the acquisition of reading and writing occurs in the initial series of an indigenous school. For the development of this research was used a bibliographic study and field research, using the technique of observation and non-systematic intervention. Field research was carried out with a quantitative and qualitative approach, based on the application of questionnaires consisting of questions for each category, and was carried out at the Municipal School of Indigenous Bekwynhmexti, located 128 km (one hundred and twenty eight kilometers) from the headquarters of the municipality of. With twenty (20) students and two (2) teachers, in order to reflect on the guiding theme that constitutes the relevance of the acquisition of reading and writing in the Bilingual teaching in the school context. Reading and writing in the initial grades arouses the curiosity of many authors who attest to its relevance in broadening the understanding and diverse linguistic advance.